A case crossover study of triggers for hand injuries in commercial fishing. Issue 5 (10th October 2007) - Kucera, K L; Loomis, D; Marshall, S W
Abstract : Objectives: Previous studies estimate hand and wrist injuries are common in commercial fishing. Risk factors including working with catch, handling gear and slips or falls, have been identified from activity and injury contact reports, but no studies have examined the influence of transient risk factors, or triggers. This case crossover study design was conducted to investigate triggers for acute hand trauma in commercial fishing. Methods: A case crossover study was nested within a previously established prospective cohort of 217 southeastern United States commercial fishermen followed from April 1999 through October 2001. Hand injury cases and controls were matched using three control selection strategies. Odds ratios (OR) and 95% confidence intervals (95% CI) were calculated to determine if transient risk factors such as glove use, engaging in more than one type of fishing, maintenance activities and other covariates of interest increased the risk of occupational traumatic hand/wrist/digit injuries. Results: 21% (46/217) of fishermen reported one or more hand/wrist/digit injuries, yielding 65 eligible cases. Performing maintenance work (any vs none) (OR 3.1, 95% CI 1.8 to 5.5) and using multiple types of fishing equipment in comparison to using only one type (OR 1.9, 95% CI 0.9 to 3.8) were associated with increased risk of hand/wrist/digit injury. There was no evidence glove use was protective (any vs none) for hand/wrist/digit injury (OR 0.9, 95% CI 0.5 to 1.7). Conclusions: The case crossover design is a useful method to determine triggers of commercial fishing-related hand/wrist/digit injuries. Maintenance work was strongly associated with hand/wrist/digit injury for these fishermen.